A vanguarda brasileira : a juventude no discurso da revista Editora do Brasil s/a (1961-1980) - Braghini, Katya Mitsuko Zuquim (2010)
This historical study presents the image of youth that was built in the 1960s and 1970s based on articles produced and published by the Revista da Editora do Brasil S/A (EBSA). Since it clearly approved the authoritarian government, this educational journal might be considered as the other side of the youth that at the time manifested in various manners. These youth manifestations resulted in the creation of a youth project organized by the editors of the journal, possibly looking for an ideal youngster who would be more convenient to the regime instituted by the military coup d état. A total of 211 reports were selected from different sections governmental reports, laws, articles from other communication channels, reports from various entities, collaborations from researchers the content of which included the terms youth , youngsters , students , within a set of 228 editions, all of them organized using a database. The documentation on which the research was based was enlarged taking into consideration other references mentioned in the Revista. The studies by Ginzburg about deciphering sources were used in speech analysis. The research indicated an intense dislike of rebelliousness and student mobilization; a generalized fear of spaces and rites being taken from adults by youngsters; a plan to cleanse youth and an idealization of a youngster that would be much more convenient as a role model for the demobilized youngsters rather than used to help adjust those who inadequately manifested their ideas